Living, training and playing in the heat: challenges to the football player and strategies for coping with environmental extremes - Maughan, R. J.; Shirreffs, S. M.; Ozgünen, K. T.; Kurdak, S. S.; Ersöz, G.; Binnet, M. S.; Dvorak, J. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Dehydration and hyperthermia both, if sufficiently severe, will impair exercise performance. Dehydration can also impair performance of tasks requiring cognition and skill. Body temperature may exceed 40 °C in competitive games played in hot weather, but limited data are available. Football played in the heat, therefore, poses a challenge, and effects on some aspects of performance become apparent as environmental temperature increases above about 12-15 °C. Prior acclimatization will reduce the impact of high environmental temperatures but provides limited protection when humidity is also high. Ingestion of fluids is effective in limiting the detrimental effects on performance: drinks with added carbohydrate and electrolytes are generally more effective than plain water and drinks may be more effective if taken cold than if taken at ambient temperature. Pre-exercise lowering of body temperature may aid some aspects of performance, but the efficacy has not been demonstrated in football.